2020
DOI: 10.1177/1740774520933362
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of social media (Facebook), targeted mailing, and in-person solicitation for the recruitment of young adult in a diabetes self-management clinical trial

Abstract: Background/Aims Research is needed to identify promising recruitment strategies to reach and engage diverse young adults in diabetes clinical research. The aim of this study was to examine the relative strengths and weaknesses of three recruitment strategies used in a diabetes self-management clinical trial: social media advertising (Facebook), targeted mailing, and in-person solicitation of clinic patients. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Snowball sampling or direct messages on media produced by these forums were, therefore, low cost and high return, although they were demographically biased recruitment strategies in our study (ie, overrepresenting optimal glycemic control and possibly other factors beyond our statistical power) and in previous work (ie, overrepresenting women and college education) [ 9 , 11 , 33 , 34 ]. Others have used news feed advertising for young adults [ 10 ], a strategy we successfully extended to middle-aged and older adults but failed to reproduce among the younger adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Snowball sampling or direct messages on media produced by these forums were, therefore, low cost and high return, although they were demographically biased recruitment strategies in our study (ie, overrepresenting optimal glycemic control and possibly other factors beyond our statistical power) and in previous work (ie, overrepresenting women and college education) [ 9 , 11 , 33 , 34 ]. Others have used news feed advertising for young adults [ 10 ], a strategy we successfully extended to middle-aged and older adults but failed to reproduce among the younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…Young adulthood (ie, 18 to 34 years old) is a time of critical health and psychosocial concerns in T1D (eg, pregnancy, transition from pediatric to adult care, and parental to personal health insurance), but consensus statements recognize that this age group is understudied in clinical trials [ 2 ]. Successful strategies for reaching this group include targeting by the age listed on social media profile [ 10 ] or medical record [ 10 , 21 ], or online support groups specific to young adults [ 9 ]. We, unfortunately, did not design our web-based methods to achieve such targeting; our news feed advertisements were targeted based on diabetes-related profile interests, which were uncommon among young adults, and the individuals who volunteered to start our snowball sampling happened to be middle-aged rather than young adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of electronic medical records (EMRs) and social media, investigators have multiple new available tools for meeting enrollment targets, such as EMR patient portal messaging 810 and targeted Facebook advertisements. 11,12 These novel strategies have the potential to reach more targeted populations faster than traditional media, such as periodicals and physically mailed advertisements. 11,13,14 However, previous literature has indicated that the use of primarily digital methods for recruitment may result in homogeneous trial samples and under-representation of minority racial groups.…”
Section: Background and Significancementioning
confidence: 99%